Customer Satisfaction Analysis On Tokopedia Marketplace Services In Jakarta Area - Rezika Lisdza Natasya; Setyo Ferry Wibowo; Terrylina Arvinta Monoarfa (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This research aims to determine the satisfaction factors of Tokopedia marketplace users in Jakarta. This research uses a quantitative approach with descriptive analysis methods. The population in this study includes individuals who currently or have used the Tokopedia marketplace. In this study, samples were taken using no-probability purposive sampling and distributing questionnaires online via Google From. The sample used in this research was 240 respondents. The sample criteria in this research consist of individuals who live in the Jakarta area, aged 17-45 years and users of the Tokopedia marketplace. This research uses validity and reliability tests as research instrument tests. This research only uses two analytical techniques, namely descriptive analysis with the aim of describing or illustrating Tokopedia marketplace user data and then classifying it so that later it can be formulated to get a clear picture of the problems that cause customers to feel satisfied. Then there is the factor analysis technique or Expolatory Factor Analysis which aims to form new factors to support customer satisfaction. This research uses the e-service quality dimension as a measurement of customer satisfaction. There are seven indicators in this research, namely, Efficiency, Fulfillment, Reliability, Privacy, Responsiveness, Compensation, Contact. The results of this research say that by using the EFA analysis technique, three factors have been formed to support customer satisfaction, the names of these three factors are: service reliability and security, customer service quality, customer comfort and efficiency.